Avaliação de estratégias de controle de potência reativa de aerogeradores síncronos em redes elétricas - NASCIMENTO, André Cavalcante do (Universidade Federal do Pará, 2011)
In the present work a methodology of reactive power injection in electric grids during voltage dips provoked by short-circuit, in connected wind farms, adopted at some countries with technological maturity in the production of wind energy in the world is evaluated. In the developed studies, the direct drive synchronous wind generator was used with full converter due to the high controllability of the converter connected to the electric grid and for possessing high capacity of reactive power supply, compared to other wind generators technologies. In Brazil, the grid code to connect wind farms to the electric grids, defined by the National Operator of the Electrical System, doesn't stipulate yet the need of adoption of such methodology during faults in the electric grid. It just specifies the ride through apability curve for voltage dips that the wind generators should follow to avoid the trip of the undervoltage relay. Criteria of the synchronous wind generators protection are evaluated starting from short-circuit simulations in a test grid with adoption of the Brazilian grid code, without reactive power injection, being compared with those of other countries that adopt reactive power injection curves.